Addressing student sexual violence in higher education : a good practice guide - DiSantis, Clarissa J.; Towl, Graham J. (Emerald Publishing Limited, 2025)
In this much anticipated second edition of their authoritative book on addressing student sexual violence at UK universities, Clarissa DiSantis and Graham Towl revisit the discussion around sexual violence within Higher Education. Students subjected to sexual violence suffer significant impacts to their physical, psychological, emotional, behavioural, and practical wellbeing, which have substantial effects on their studies. Higher Education Institutions (HEIs) have a duty to ensure students can access their education in environments that are safe - without fear, harassment, or violence. Providing how-to level information on staffing, policy writing, responding to disclosures, developing comprehensive prevention and response education programmes, conducting trauma-informed investigations, adjudication and sanctioning processes, and offering sanctioning guidelines for sexual violence, new chapters include: Technology-Facilitated Sexual Violence and Technology-Facilitated Solutions: Learning After COVID-19; Tackling Resistance to Change; Case Management and Practitioner Safety; When Universities Get It Wrong; and Leadership and Partnerships. This is a ground-breaking resource for practitioners, senior leaders, policy makers, student services administrators, educators, investigators, adjudicators, and activists in Higher Education. It will undoubtedly be of use to those tasked with ensuring Office for Students regulatory compliance in 2025 and beyond.
Keywords: Sex crimes.; Universities and colleges -- Safety measures.; Education -- Administration -- Higher.; Higher education, tertiary education.; Educational administration and organization.; elektronické knihy; electronic books